EDUKASI BELAJAR MEMBACA MENGGUNAKAN TEKNOLOGI SPEECH RECOGNITION - Reza Zubaedah Reza Zubaedah; Hasanudin Jayawardana Hasanudin Jayawardana; Yuni Yuvensius Tonem Yuni Yuvensius Tonem (Ikatan Dosen Menulis, 2022)
One of the problem with learning facilities, teachers in teaching are still using conventional methods where teachers provide material to students according to the 2013 curriculum standards, namely using thematic books by inviting students to directly participate directly in learning while students who cannot read and pronounce letters properly The teacher must provide separate time for students. In this research the development method used is Waterfall planning, analysis, design, implementation, and the final stage, namely. making applications with the Speech Recognition Method. The results of the research are in the form of media applications for learning to read using speech recognition technology on smartphones based on learning media that presents letters of the alphabet, recognizes consonants, recognizes vowels and games in the form of guessing words and finding pairs of pictures